PENGARUH KEDISIPLINAN DAN KETANGGAPAN TERHADAP KEPUASAN PELANGGAN DENGAN KUALITAS PELAYANAN SEBAGAI VARIABEL INTERVENING - Agus Budi Purwanto; Susanti Wahyuningsih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2013)
The background of this research is the declining number of hotels in semarang district. This indicates that the hotel can not satisfy customers. In general, this study aimed to determine the effect of directly or indirectly discipline and responsiveness to customer satisfaction where the quality of service as a mediating variable. So that it can be seen that the most powerful mediating pathways to influence customer satisfaction. Specifically, this research aims to increase the number of visitors hotels in semarang district. Research data collection techniques by spread many questionnaires to the hotel customers in semarang district are arranged systematically with multiple choice answers which easy to understand. Distribution of the questionnaires by means of a direct encounter conducted in the period April-July, 2013, with a sample of some 250 people. Then the data were collected through the questionnaires to be tested the data analyst; validity and reliability, followed by pathway analysis (path analysis), test the strength of the model using SEM (Structural Equation Modeling). The result of the research proves that there is positive direct influence between discipline and responsiveness to customer satisfaction. The results also shows that the quality of service is a positive intervening between discipline and responsiveness towards customer satisfaction.